Poultry manure fertilization of Egyptian aquaculture ponds brings more cons than pros - Nyberg, Oskar; Novotny, Andreas; Sbaay, Ashraf; Nasr-Allah, Ahmed; Al-Kenawy, Diaa; Rossignoli, Cristiano; Henriksson, Patrik (Elsevier, 2024)
Aquaculture is a crucial sector for Egyptian food production, providing a cheap source of animal protein while securing income and employment for a substantial part Egypt's population. Nile tilapia (Oreochromis niloticus) is the most commonly produced fish, usually farmed in earthen ponds around the Northern Delta Lakes. A common practice among farms is to fertilize ponds with chicken manure (CM) in order to increase nutrient levels and promote phytoplankton, consumed by the fish. However, with reports of use of antibiotics in Egypt's poultry sector, and that CM contains residues of antibiotics, antibiotic resistant pathogens and antibiotic resistance genes (ARGs) are production benefits large enough to compensate a potential health hazard?